2011
DOI: 10.1029/2011ja017213
|View full text |Cite
|
Sign up to set email alerts
|

Topside equatorial ionospheric density and composition during and after extreme solar minimum

Abstract: During the recent solar minimum, solar activity reached the lowest levels observed during the space age. This extremely low solar activity has accompanied a number of unexpected observations in the Earth's ionosphere‐thermosphere system when compared to previous solar minima. Among these are the fact that the ionosphere is significantly contracted beyond expectations based on empirical models. Altitude profiles of ion density and composition measurements near the magnetic dip equator are constructed from the C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
66
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 33 publications
8
66
0
Order By: Relevance
“…However, it was active on 21 January 2010 and the transition altitude of around 525 km was deduced from CINDI versus around 550-575 km from the ISR. Finally, this is also consistent with globally averaged CINDI observations reported by Klenzing et al (2011aKlenzing et al ( ) from 2009Klenzing et al ( and 2010, which showed the transition height between 500 and 600 km in the pre-midnight local time sector.…”
Section: Datasupporting
confidence: 80%
“…However, it was active on 21 January 2010 and the transition altitude of around 525 km was deduced from CINDI versus around 550-575 km from the ISR. Finally, this is also consistent with globally averaged CINDI observations reported by Klenzing et al (2011aKlenzing et al ( ) from 2009Klenzing et al ( and 2010, which showed the transition height between 500 and 600 km in the pre-midnight local time sector.…”
Section: Datasupporting
confidence: 80%
“…Since ground measurements are more frequent and reliable than above the F-peak, it is not surprising that IRI is less accurate for the topside ionosphere. Additionally, unlike radar networks and ground-based ionosonde data that usually imply constant latitude and longitude, topside ionosonde [e.g., Benson and Bilitza, 2009] and in situ measurements [e.g., Klenzing et al, 2011] are trajectory dependent. Most likely, corrections to plasma density during the 23/24 solar minimum are also necessary below the F-peak, as suggested by IVM measurements above 400 km [Klenzing et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Results of configuration M4 are not shown because we cannot provide reasonable estimates of the local transverse heterogeneity. Model parameters are evaluated against electron density and ion composition profiles considering various constraints from IRI and the Ion Velocity Meter (IVM) data recorded onboard C/NOFS: (P0) IRI-2007 default parameterization; (P1) IRI density profile normalized against IVM plasma density recorded during fingerprint observation (altitude $500 km); (P2) IRI density and ion composition profiles normalized against IVM data under conditions defined in P1; (P3) composite electron density profile combining IVM mean density in the altitude range between 400 and 850 km (a full discussion of the monthly and seasonal averages can be found in Klenzing et al [2011]) and IRI elsewhere; (P4) composite electron density and ion composition profiles under conditions defined in P3; (P5) profile similar to P4 but with the IVM density distribution decreased by one standard deviation; (P6) IRI-2011 default parameterization. Since the density profiles cannot be fully reconstructed from 2008 due to uneven data coverage, the June solstice 2009 values are used for the purpose of this study; this is nevertheless appropriate because measurements during 2008 and 2009 are closer to each other than they are to the IRI predictions for either year.…”
Section: Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some big deviations were revealed between the in-situ N e detected by satellites at a certain altitude and N e by the IRI model, especially in equatorial areas with the equatorial ionization anomaly (EIA), such as CHAMP, GRACE, Hinotori, and DMSP (Watanabe et al 1995;Bhuyan et al 2003;Lei et al 2007;Liu et al 2007a;Kakinami et al 2008;Lühr and Xiong 2010), while these satellite data have been contributing to improve the IRI model in turn. Due to these differences, new efforts are underway to improve the IRI model using C/NOFS, CHAMP and ionosonde data (Klenzing et al 2011(Klenzing et al , 2013Bilitza et al 2012).…”
Section: Introductionmentioning
confidence: 99%